Photoactivation of Butyric Acid from 6‐Aminobenzocoumarin Cages. Issue 27 (September 2015) - Soares, Ana M. S.; Hungerford, Graham; Costa, Susana P. G.; Gonçalves, M. Sameiro T.
Abstract: A new benzocoumarin bearing an amino group is proposed as a photocleavable protecting group for carboxylic acids. The novel heterocycle, 6‐amino‐4‐chloromethyl‐2‐oxo‐2 H ‐naphtho[1, 2‐ b ]pyran was used in the preparation of ester conjugates of butyric acid, and of the corresponding mono‐ and dimethylated or ethylated derivatives. The photolability of the ester conjugates was studied by irradiation at selected wavelengths in methanol/HEPES buffer (80:20) solutions, and the release of butyric acid was followed with HPLC/UV and 1 H NMR monitoring. Release of the carboxylic acid was faster for the monoalkylated derivatives (approximately within 20 min), at the longer wavelengths of irradiation (350 and 419 nm). The photophysics of the heterocyclic conjugates was also evaluated by both steady state and time‐resolved methods. Abstract : Butyric acid was released from new aminobenzocoumarin ester cages in a photoinduced process employing UV/Vis light.